Correlation between Job Demands, Work Meaningfulness, Job Stress, and Turnover Intention: Empirical Study in Public Sector Organizations - Yulabi, Ruchan; Anggara, Widi Galih; Istiqomah, Iis (Universitas Negeri Malang, 2023)
This study aimed to test the relationship between job demand, work meaningfulness, and turnover intention with job stress as a mediating variable. A population of 1310 officers from a government unit were asked to complete questionnaires (which consisted of 32 questions adapted from previous research) employing a cross-sectional study approach. The final sample consisted of 383 responses, and regression analysis with Macro PROCESS was used to test the hypotheses. The findings indicate that job stress was positively correlated with job demands, but negatively correlated with work meaningfulness. Further, this study found that job stress positively correlated with turnover intention and was a mediating variable in the relationship between job demand, work meaningfulness, and turnover intention. This study implies that to lower turnover intention, organizations may decrease job demand and stress levels and improve work meaningfulness.